Detection and genotyping of human papillomavirus (HPV) in HIV-infected women and its relationship with HPV/HIV co-infection. Issue 14 (April 2018) - Badial, Rodolfo Miglioli; Dias, Marina Carrara; Stuqui, Bruna; Melli, Patrícia Pereira dos Santos; Quintana, Silvana Maria; Bonfim, Caroline Measso do; Cordeiro, José Antônio; Rabachini, Tatiana; Calmon, Marilia de Freitas; Provazzi, Paola Jocelan Scarin; Rahal, Paula
Abstract : Abstract: HPV have been identified as high-risk and low-risk, depending on their association with the development of cancer. HPV infections can be facilitated by co-infection with HIV. Here, we investigated HPV prevalence and genotypes and the risk factors affecting HPV/HIV co-infection. Forty HIV-positive patients had 80 cervical swab samples collected in 2 consecutive years. Polymerase chain reaction and DNA direct sequencing were used to perform HPV genotyping. Statistical analyses were performed regarding risk factors for HPV/HIV co-infection and the occurrence of cervical lesions. HPV DNA was detected in 59 samples (73.75%), and high-risk HPVs were predominant (59.3%). The most prevalent type was HPV56 (17%), followed by HPV16 (15.3%). Patient age did not affect the risk of cervical cancer ( P  = .84) or HPV prevalence in different years ( P  = .25/ P  = .63). CD4 count also did not affect the risk for cervical lesions in the tested samples ( P  = .15/ P  = .28). Although the HIV viral load was not correlated with an increase in cervical lesion detection in the first group of analyzed samples ( P  = .12), it did affect cervical cancer risk in the group of samples analyzed in the following year ( P  = .045). HIV-infected patients presented a high prevalence of HPV co-infection, and HPV16 and HPV56 were the most prevalent genotypes. Considering this, it is possible that immunodeficiency can contribute to increased susceptibility to HPV56 infection in HIV-infected patients. The association between HIV viral load and the lesions also confirmed the importance of monitoring HIV/HPV co-infected patients with high HIV viral loads.